การระบุเพศและอาณาเขตที่อยู่อาศัยของนกเค้ากู่ Otus lettia (Hodgson, 1836) ที่เกาะแสมสาร จังหวัดชลบุรี - ศักรินทร์ แสนสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
The morphometric study of 48 Collared Scops Owls from the museum specimens (30 males, 18 females) revealed three sexual dimorphic characters which were wing length, second digit length and second claw length. These characters were used to generate the sex-predicting equations with accuracy up to 66.7 – 79.2%. Radio-tracking study of Collared Scops Owls at Samaesan Island (2 adults and 1 juvenile) during April 2015 – May 2016 found that in one year the adult home range sizes in terms of 100% MCP and 95% AK were 0.0371-0.0482 and 0.0198-0.0242 km2, respectively, and the core area sizes in terms of 75% AK and 50% AK were 0.0029-0.0082 and 0.0006-0.0035 km2, respectively. Although these adult owls utilized the same area throughout the year, the owl’s home range in breeding season (January - April; 100% MCP, 75% AK and 50% AK were 0.0221-0.0260, 0.0107-0.0122 and 0.0044-0.0050 km2, respectively) was smaller but not the core area which was larger than in non-breeding season (May – December; 100% MCP, 95% AK, 75% AK and 50% AK were 0.0344-0.0361, 0.0162-0.0214, 0.0024-0.0051 and 0.0005-0.0014 km2, respectively). The juvenile owl did not have its own apparent home range and core area for roosting during the day (100% MCP, 75% AK and 50% AK were 0.0449-0.0488, 0.0403 and 0.0180 km2, respectively) which were larger than those in adults (100% MCP, 75% AK and 50% AK were 0.0117-0.0146, 0.0006-0.0007 and 0.0003 km2, respectively). While late juvenile home range and core area during nighttime were similar in size to those in adults (100% MCP, 95% AK, 75% AK and 50% AK were 0.0367-0.0481, 0.0282-0.0370, 0.0101-0.0115 and 0.0036-0.0050 km2, respectively), juvenile home range and core area were much larger. The dietary study using pellets and camera traps showed that Collared Scops Owls mostly consumed insects in 5 Orders (Hemiptera, Orthoptera, Blattodea, Coleoptera and Lepidoptera) and centipede (Order Scolopendromorpha). Parents mostly brought preys back to roost and feed their fledglings around dusk (8:01-9:00 pm) and dawn (3:01-4:00 am)